Antibacterial Activity of Ethanolic Extract, n-Hexane Fraction, and Chloroform Fraction of Binahong Leaves (Anredera Cordifolia) on Escherichia Coli and its Phytochemical Screening - Pramita Yuli Pratiwi; Ana Mardiyaningsih; Nur Ismiyati; Hery Setiyawan (Tropical Biopharmaca Research Center, IPB University, 2021)
Binahong leaves (Anredera cordifolia (Ten.) Steenis) are known to contain antibacterial activity compounds. The compounds contained in binahong leaves include flavonoids, alkaloids, saponins, and tannins. Escherichia coli is a gram-negative bacteria that often causes infections such as diarrhea. The purpose of this study was to determine the effect of ethanolic extract, n-hexane fraction, and chloroform fraction of binahong leaves on the growth of Escherichia coli bacteria and its phytochemical screening This research used ethanolic extract, hexane fraction and chloroform fraction of binahong leaves against Escherichia coli bacteria with concentrations of 12.5, 25 and 50% The positive control was chloramphenicol and the negative control was DMSO The method used disk diffusion technique, marked the presence of clear areas around the paper disc that showed an obstacle to bacterial growth phytochemical screening of alkaloids, flavonoids, saponins and tannins using a test tube. The result showed antibacterial activity against the growth of Escherichia coli with the diameter of the inhibition zone at concentrations of 12.5, 25, and 50%, namely the hexane fraction of 8.16; 9.73 and 12.93 mm. At the chloroform fraction 7.67; 8.47 and 9.87 mm. and the ethanolic extract of 7.33; 9.95 and 13.32 mm. The result of the largest inhibition zone was the ethanolic extract of binahong leaves with a concentration of 50%. The results of phytochemical screening using a test tube showed that the compounds contained in the ethanolic extract were flavonoids, alkaloids, saponins, and tannins.